Academic Stress And Suicidal Ideation Among Undergraduates In Kwara State - Elizabeth Obianwego Uyanne (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Academic stress is a product of a combination of all academic related demands that exceed the adaptive resources available to students in the university. The purpose of this study is to investigate the relationship between academic stress and suicidal ideation among undergraduates in Kwara State. Descriptive survey design of a correlational type was adopted for the study. The population of the study comprised all undergraduates’ students in Kwara State. 200 Students were randomly selected to participate in the study from four universities. The finding reveal that the causes of academic stress among university undergraduates in Ilorin are academic workloads; difficulty of time between study and social activity; dealing with difficult course; submission deadlines of assignments/projects; feel threatened by Grade Point Average on portal; lack of relevant course materials; difficulty to cover the course outline among others. The result would illuminate University undergraduates to always find balance between study time and social activities which academically constitute so much stress.